Measurement of the branching fraction of D + → τ + ν τ - Ablikim, M; Achasov, MN; Adlarson, P; Afedulidis, O; Ai, XC; Aliberti, R; Amoroso, A; Bai, Y; Bakina, O; Balossino, I; Ban, Y; Bao, H; et al. (Springer, 2025)
By analyzing e+e− collision data with an integrated luminosity of 7.9 fb−1 collected with the BESIII detector at the center-of-mass energy of 3.773 GeV, the branching fraction of D+→ τ+ντ is determined as B = (9.9 ± 1.1stat± 0.5syst) × 10−4. Using the most precise result B(D+→ μ+νμ) = (3.981 ± 0.079stat± 0.040syst) × 10−4 [1], we determine Rτ/μ = Γ(D+ → τ+ντ)/Γ(D+ → μ+νμ) = 2.49 ± 0.31, achieving a factor of two improvement in precision compared to the previous BESIII result. This measurement is in agreement with the standard model prediction of lepton flavor universality within one standard deviation.